Altered Gut Microbiota Is a Novel Mechanism for the Adverse Effects Induced by Foodborne Titanium Dioxide Nanoparticles in Obese and Non-obese Mice (P21-021-19). (13th June 2019) - Du, Hengjun; Cao, Xiaoqiong; Han, Yanhui; Gu, Min; Xiao, Hang
Abstract: Objectives: Many food products contain inorganic nanoparticles (NPs), such as titanium dioxide (TiO2 ) NPs. There is increasing concern about the potential unintended health risks associated with foodborne TiO2 NPs in certain populations, such as the obese. The purpose of this study was to determine the adverse effects of TiO2 NPs in obese individuals, the molecular mechanism involved and the potential role of gut microbiota in mediating the adverse effects. Methods: Two types of TiO2 (30 nm and E171-Food grade TiO2 ) were mixed with mouse diet at 0.1 wt% and fed to two populations of mice (high-fat diet-fed obese mice and non-obese mice). Meanwhile, fecal samples from the above groups of mice were collected weekly for transplanting to four groups of mice fed a low-fat diet for 10 weeks. 16 s rRNA gene amplicon sequencing, histological analysis, immunohistochemistry, ELISA and SCFAs analysis were utilized to characterize the composition of the microbiota, inflammation status, and the effects of altered gut microbiota on the inflammation status of the mouse colon. Results: TiO2 NPs significantly altered the composition of gut microbiota with stronger alterations in the high-fat diet-fed obese mice than the low-fat diet-fed non-obese mice. The abundance of inflammation-related cytokines (e.g., IL-10, IL-12p70, and IL-17) and myeloperoxidase (MPO) in the mouse colonic mucosa were significantly altered by TiO2 NPs to produce an inflammatory state. TiO2 NPs decreased the cecal levels of SCFAs such as butyrate. Moreover, the magnitude of the above alteration was higher in the obese mice than in the non-obese mice. After 10 weeks of microbial transplant, microbiota from the mice consuming a high-fat diet with TiO2 NPs led to an increase of pro-inflammatory cytokines, loss of healthy colonic morphology, and infiltration of immune cells in the colon of the low-fat diet-fed recipient mice, indicating a significant colonic inflammation. Conclusions: TiO2 NPs altered gut microbiota in both obese and non-obese mice, with stronger effects in the obese mice, and the alteration of gut microbiota led to colonic inflammation in the mice. Overall, these findings provided a valuable new perspective on the potential adverse effects and appropriate mechanisms of foodborne TiO2 NPs among populations with different obese status. Funding Sources: USDA/NIFA competitive grants to Hang Xiao.